Through the Methodological View of the Historiographic Discussion of Mid-1990s - Atanasova, Veselina (Research Papers, 2015)
At the centre of the present study is shedding some additional light for the further clarification of the concepts of “whig” and “counter-whig” in the historiography of economics. The focus is on the relation (partial coverage in the content or other crossings) of the concepts of the absolutist and the relativist approaches and the corresponding types of history, the internalist and the externalist approaches and the corresponding kinds of history, and especially on the relation between “whig” and “contra-whig” types of history of economics in the light and in the context of the envisioned relations. The study is based on an electronic publication in December 1996 of selected by Esther-Mirjam Sent postings of historians of economics, intellectual historians, etc., who have taken participation in the discussion, the rise of which was given by a Guest editorial of James P. Henderson (November 1996) “Whig History is Dead – Now What?”, addressed to the attention of the members of the History of Economics Society.The central message argued through the view of this discussion is in a direction of conceptualizing a relatively holistic historiographic approach, reviving the role of the History of Economics in constructing contemporary social-economic theory and against the divide and tearing apart the unity of methodology of economics, history of economics and economics.JEL:B00; B20; B40; B49
Keywords: Whig and contra-whig history of economics; Absolutist and relativist approaches/ histories; Internalist and externalist approaches/histories; Intellectual history; Role of history of economics; Unity of methodology of economics; History of economics and contemporary economics; Geistesgeschichte